Fluopsin C Promotes Biofilm Removal of XDR Acinetobacter baumannii and Presents an Additive Effect with Polymyxin B on Planktonic Cells - Leandro Afonso; Kathlen Giovana Grzegorczyk; Julio Martins Salomão; Kawany Roque Basso; Leonardo Cruz Alves; Maria Clara Davis Silva; Andreas Lazaros Chryssafidis; Bárbara Gionco-Cano; Sueli Fumie Yamada-Ogatta; Galdino Andrade (MDPI AG, 2024)
Acinetobacter baumannii emerged as one of the most important pathogens for the development of new antimicrobials due to the worldwide detection of isolates resistant to all commercial antibiotics, especially in nosocomial infections. Biofilm formation enhances A. baumannii survival by impairing antimicrobial action, being an important target for new antimicrobials. Fluopsin C (FlpC) is an organocupric secondary metabolite with broad-spectrum antimicrobial activity. This study aimed to evaluate the antibiofilm activity of FlpC in established biofilms of extensively drug-resistant A. baumannii (XDRAb) and the effects of its combination with polymyxin B (PolB) on planktonic cells. XDRAb susceptibility profiles were determined by Vitek 2 Compact, disk diffusion, and broth microdilution. FlpC and PolB interaction was assessed using the microdilution checkerboard method and time-kill kinetics. Biofilms of XDRAb characterization and removal by FlpC exposure were assessed by biomass staining with crystal violet. Confocal Laser Scanning Microscopy was used to determine the temporal removal of the biofilms using DAPI, and cell viability using live/dead staining. The minimum inhibitory concentration (MIC) of FlpC on XDRAb was 3.5 µg mL−1. Combining FlpC + PolB culminated in an additive effect, increasing bacterial susceptibility to both antibiotics. FlpC-treated 24 h biofilms reached a major biomass removal of 92.40 ± 3.38% (isolate 230) using 7.0 µg mL−1 FlpC. Biomass removal occurred significantly over time through the dispersion of the extracellular matrix and decreasing cell number and viability. This is the first report of FlpC's activity on XDRAb and the compound showed a promissory response on planktonic and sessile cells, making it a candidate for the development of a new antimicrobial product.